2022
DOI: 10.3389/frspt.2022.792944
|View full text |Cite
|
Sign up to set email alerts
|

ET-Class: An Energy Transfer-Based Classification of Space Debris Removal Methods and Missions

Abstract: Space debris is positioned as a fatal problem for current and future space missions. Many effective space debris removal methods have been proposed in the past decade, and several techniques have been either tested on the ground or in parabolic flight experiments. Nevertheless, no uncooperative debris has been removed from any orbit until this moment. Therefore, to expand this research field and progressing the development of space debris removal technologies, this paper reviews and compares the existing techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 145 publications
0
9
0
Order By: Relevance
“…The hybrid compliance's length l m is equal to 0.05m since it is the sum of two lengths: l m = l s + l a ; the length l s of the passive physical compliance, equal to 0.025 m, and the maximum displacement l a of the linear actuators' moving parts, equal to 0.025 m. The schematic of the system under simulation study as designed in Simscape is shown in Figure 15. The algorithm runs for the range of stiffness values k m between [0.1-0.5] N/m, with a step of 0.1 N/m, for a range of space debris mass m d between [1-100] kg, with a step of 1 kg, and for a range of minimum contact time t c required for completion of the capturing between [4][5][6][7][8][9][10][11][12] s, with steps of 2 s.…”
Section: Debris-mass and Compliance Relationmentioning
confidence: 99%
See 4 more Smart Citations
“…The hybrid compliance's length l m is equal to 0.05m since it is the sum of two lengths: l m = l s + l a ; the length l s of the passive physical compliance, equal to 0.025 m, and the maximum displacement l a of the linear actuators' moving parts, equal to 0.025 m. The schematic of the system under simulation study as designed in Simscape is shown in Figure 15. The algorithm runs for the range of stiffness values k m between [0.1-0.5] N/m, with a step of 0.1 N/m, for a range of space debris mass m d between [1-100] kg, with a step of 1 kg, and for a range of minimum contact time t c required for completion of the capturing between [4][5][6][7][8][9][10][11][12] s, with steps of 2 s.…”
Section: Debris-mass and Compliance Relationmentioning
confidence: 99%
“…The resulting diagram is shown in Figure 16, providing the relation between these variables. More detailed visualization of the data of Figure 16 is provided for each contact time in the range of [4][5][6][7][8][9][10][11][12] s in Appendix A. The lines depicted in the 3D diagram correspond to points in 3D space, representing the successful cases obtained from the algorithm.…”
Section: Debris-mass and Compliance Relationmentioning
confidence: 99%
See 3 more Smart Citations